The Relationship between Family Smoking Habits and Tuberculosis Incidence in Children Aged 3-6 Years in Bandung Regency - Tambunan, Irisanna; Nanda, Shely Novia; Suprapti, Tuti (International Journal of Global Operations Research, 2023)
Childhood tuberculosis in Indonesia is the third most common in the world, in 2020 the number of new child Tuberculosis cases decreased by 32.4%, this is still far from the government's target in 2024, which is 90%. Bandung Regency has 62 health centers, the highest number of child TB cases is at the Linggar Health Center, namely 42 children with Tuberculosis due to family factors that have smoking habits. The aim of the study was to determine the relationship between family smoking habits and the incidence of Tuberculosis in children aged 3–6 years in the Working Area of the Linggar Health Center. This type of research uses casecontrol with a population of 60 families with children aged 3-6 years. The sampling technique used purposive sampling, the sample is 60 families. Data collection using the Riskesdas 2018 questionnaire. Data analysis used univariate and bivariate analysis. The results of the study most of the cases (76.7%) were smokers while the controls (60%) were non-smokers. Family smoking status (P-value 0.004), type of white cigarette (P-value 0.002), number of cigarettes <12 cigarettes (P-value 0.006), duration of smoking > 19 minutes (P-value 0.000), and smoking in the house (P- value 0.001) has a relationship with TB in children. Of the five, smoking duration >19 minutes is the riskiest for TB in children (OR 19,286) because the longer the duration of family smoking, the more influential it is on the incidence of tuberculosis in children aged 3-6 years considering the content of smoking can reduce children's immunity. The conclusion of the study is that there is a relationship between family smoking habits and TB in children aged 3-6 years in the Working Area of the Linggar Health Center.